2021
DOI: 10.3389/fvets.2020.539444
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Genetic Relatedness of Brucella Strains in Countries Along the Silk Road

Abstract: In this study, MLVA (multiple-locus variable-number tandem repeat analysis) genotype data of Brucella strains from 11 countries along the Silk Road were downloaded from the MLVAbank. MLVA data of strains were applied to the constructed Minimum Spanning Tree to explore the species/biovars distribution, geographic origins, and genetic relationships of the strains analyzed. Moreover, whole-genome sequencing–single-nucleotide polymorphism (WGS-SNP) phylogenetic analysis of the genome of Brucella melitensis strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Omitting the highly homoplastic VNTR markers from a cluster analysis may increase the phylogenetic meaning of such an analysis and can be helpful to interpret the general regional relationships of Brucella spp. worldwide [ 38 ]. The other panel included in the MLVA-16 consists of minisatellites with varying sequences between the primer binding sites [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Omitting the highly homoplastic VNTR markers from a cluster analysis may increase the phylogenetic meaning of such an analysis and can be helpful to interpret the general regional relationships of Brucella spp. worldwide [ 38 ]. The other panel included in the MLVA-16 consists of minisatellites with varying sequences between the primer binding sites [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report described the analyses of the species distribution, host lineage profiles, genetic relatedness, and the epidemiological correlation of the Brucella species in countries along the Silk Road. The authors concluded that numerous animal reservoirs were a potential reason for the continuous circulation of the brucellosis in the examined countries, while the B. abortus strains were dominated in these countries and spreading within the national borders (23). In addition, using descriptive analysis and meta-analysis approaches, Zhou et al reported very recently that dogs and yaks were the leading reservoirs and emerging hosts for Brucella transmission in China (24).…”
Section: Discussionmentioning
confidence: 99%
“…and product, and sharing of the pastureland among these countries, are reasonable explanations (Liu, Wang, Wei, et al, 2020). In addition, Sükhbaatar is located east of Mongolia and shows a high prevalence of human brucellosis that reached 22.6% (72/318) incidence during the 2010-2012 period (Tsend et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Hulun Buir is adjacent to many countries, and strains in these regions share a common geographical origin. Frequent exchange and trade of animals (sheep and goats) and product, and sharing of the pastureland among these countries, are reasonable explanations (Liu, Wang, Wei, et al, 2020). In addition, Sükhbaatar is located east of Mongolia and shows a high prevalence of human brucellosis that reached 22.6% (72/318) incidence during the 2010–2012 period (Tsend et al., 2014).…”
Section: Discussionmentioning
confidence: 99%